Risk of complications in patients who are obese following upper limb arthroplasty: A systematic review and meta-analysis - Theodoulou, A; Krishnan, J; Aromataris, E (Elsevier, 2020)
Purpose A systematic review was performed to investigate the impact of obesity on complications following total shoulder arthroplasty (TSA), reverse total shoulder arthroplasty (RTSA) and total elbow arthroplasty (TEA).